Entropy of the Shift on II₁-representations of the Group S(∞) - Boyko, M.S.; Nessonov, N.I. (Український математичний вісник, 2005)
We have obtained the explicit formulae for the CNT-entropy of the shift on II₁-representations of the infinite symmetric group S(∞) in terms of Thoma-parameters.